1999
DOI: 10.1089/acm.1999.5.529
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine and Psychologic Factors: Toward an Individual Differences Model of Complementary and Alternative Medicine Use and Outcomes

Abstract: Above average use of CAM is associated with higher education, greater well-being and higher Absorption. The personality traits associated with alternative therapies are compatible with participation in these therapies and may facilitate the capacity to benefit from them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 55 publications
1
35
0
2
Order By: Relevance
“…For example, in a study of cancer patients [13], active coping style and religiousness, but not lack of social support or information, were significantly associated with increased use of CAM. Using the Tellgen Absorption Scale (TAS), another study conducted among clinical and community samples [10] found absorption, 1 which is known to be positively correlated with the trait of ''openness to experience'' [14], to be an independent predictor of CAM use. Because most patients make choices about CAM use without guidance from a conventional care provider, their own psychosocial characteristics may play a much greater role in their CAM use than in their conventional medical care.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study of cancer patients [13], active coping style and religiousness, but not lack of social support or information, were significantly associated with increased use of CAM. Using the Tellgen Absorption Scale (TAS), another study conducted among clinical and community samples [10] found absorption, 1 which is known to be positively correlated with the trait of ''openness to experience'' [14], to be an independent predictor of CAM use. Because most patients make choices about CAM use without guidance from a conventional care provider, their own psychosocial characteristics may play a much greater role in their CAM use than in their conventional medical care.…”
Section: Introductionmentioning
confidence: 99%
“…Several psychological factors predict the use of CAM [18], including health beliefs [19]. There is evidence that CAM users are higher on trait absorption [20] and on spirituality [21]. The association with absorption is interesting in view of the research, cited above, showing that absorption in a coping strategy (i.e., task specific rather trait absorption) predicts outcome independently of expectancy [11,12].…”
mentioning
confidence: 99%
“…15 Thus, high Absorption scorers have enhanced self-regulation capacities that might be engaged toward a therapeutic outcome. However, as Tellegen has described, the effects of high Absorption can go in either a positive or negative direction, depending on the situation, and this interaction may be manifest in the complexities of placebo phenomena.…”
Section: Introductionmentioning
confidence: 99%